Current Perspectives on Psoriasis and Its Therapeutic Approaches: A Comprehensive Review - Oleksy, Daria; Hermanowicz, Kamil; Kaczmarska, Urszula; Woźniak, Aleksandra; Cioch , Michał Jakub; Nowak, Julia; Doman , Katarzyna; Mycyk , Marcin; Najdek, Agnieszka; Komada, Dawid (Journal of Education, Health and Sport, 2025)
Psoriasis is a chronic inflammatory skin disorder characterized by an accelerated keratinocyte cell cycle, leading to the formation of scaly plaques. The pathogenesis of psoriasis involves complex interactions between immune system cells and keratinocytes, with a key role played by T lymphocytes. Genetic and environmental factors play a significant role in the development of the disease.